Experience the convenience of getting your questions answered at IDNLearn.com. Receive prompt and accurate responses to your questions from our community of knowledgeable professionals ready to assist you at any time.
Sagot :
To solve the given system of linear equations using Gaussian elimination with back-substitution, we will follow these steps:
1. Write the augmented matrix for the system of equations:
[tex]\[ \begin{aligned} 3x - 2y + z &= 11 \\ -x + y + 2z &= -11 \\ x - y - 4z &= 17 \end{aligned} \][/tex]
The augmented matrix representing this system is:
[tex]\[ \left[\begin{array}{ccc|c} 3 & -2 & 1 & 11 \\ -1 & 1 & 2 & -11 \\ 1 & -1 & -4 & 17 \end{array}\right] \][/tex]
2. Perform Gaussian elimination to transform the matrix into an upper triangular form.
- Normalize the first row by dividing by the pivot element (3):
[tex]\[ \left[\begin{array}{ccc|c} 1 & -0.6667 & 0.3333 & 3.6667 \\ -1 & 1 & 2 & -11 \\ 1 & -1 & -4 & 17 \end{array}\right] \][/tex]
- Eliminate the entries below the pivot in column 1:
[tex]\[ \left[\begin{array}{ccc|c} 1 & -0.6667 & 0.3333 & 3.6667 \\ 0 & 0.3333 & 2.3333 & -7.3333 \\ 0 & -0.3333 & -4.3333 & 13.3333 \end{array}\right] \][/tex]
- Normalize the second row by dividing by the pivot element (0.3333):
[tex]\[ \left[\begin{array}{ccc|c} 1 & -0.6667 & 0.3333 & 3.6667 \\ 0 & 1 & 7 & -22 \\ 0 & -0.3333 & -4.3333 & 13.3333 \end{array}\right] \][/tex]
- Eliminate the entries below the pivot in column 2:
[tex]\[ \left[\begin{array}{ccc|c} 1 & -0.6667 & 0.3333 & 3.6667 \\ 0 & 1 & 7 & -22 \\ 0 & 0 & -2 & 6 \end{array}\right] \][/tex]
- Normalize the third row by dividing by the pivot element (-2):
[tex]\[ \left[\begin{array}{ccc|c} 1 & -0.6667 & 0.3333 & 3.6667 \\ 0 & 1 & 7 & -22 \\ 0 & 0 & 1 & -3 \end{array}\right] \][/tex]
3. Perform back-substitution to find the values of [tex]\(x, y,\)[/tex] and [tex]\(z\)[/tex].
- From the third row:
[tex]\[ z = -3 \][/tex]
- Substitute [tex]\(z = -3\)[/tex] into the second row equation:
[tex]\[ y + 7(-3) = -22 \implies y - 21 = -22 \implies y = -1 \][/tex]
- Substitute [tex]\( y = -1 \)[/tex] and [tex]\( z = -3 \)[/tex] into the first row equation:
[tex]\[ x - 0.6667(-1) + 0.3333(-3) = 3.6667 \implies x + 0.6667 - 1 = 3.6667 \implies x + 0.6667 = 4.6667 \implies x = 4 \][/tex]
So, the solution to the system of equations is:
[tex]\[ (x, y, z) = (4, -1, -3) \][/tex]
1. Write the augmented matrix for the system of equations:
[tex]\[ \begin{aligned} 3x - 2y + z &= 11 \\ -x + y + 2z &= -11 \\ x - y - 4z &= 17 \end{aligned} \][/tex]
The augmented matrix representing this system is:
[tex]\[ \left[\begin{array}{ccc|c} 3 & -2 & 1 & 11 \\ -1 & 1 & 2 & -11 \\ 1 & -1 & -4 & 17 \end{array}\right] \][/tex]
2. Perform Gaussian elimination to transform the matrix into an upper triangular form.
- Normalize the first row by dividing by the pivot element (3):
[tex]\[ \left[\begin{array}{ccc|c} 1 & -0.6667 & 0.3333 & 3.6667 \\ -1 & 1 & 2 & -11 \\ 1 & -1 & -4 & 17 \end{array}\right] \][/tex]
- Eliminate the entries below the pivot in column 1:
[tex]\[ \left[\begin{array}{ccc|c} 1 & -0.6667 & 0.3333 & 3.6667 \\ 0 & 0.3333 & 2.3333 & -7.3333 \\ 0 & -0.3333 & -4.3333 & 13.3333 \end{array}\right] \][/tex]
- Normalize the second row by dividing by the pivot element (0.3333):
[tex]\[ \left[\begin{array}{ccc|c} 1 & -0.6667 & 0.3333 & 3.6667 \\ 0 & 1 & 7 & -22 \\ 0 & -0.3333 & -4.3333 & 13.3333 \end{array}\right] \][/tex]
- Eliminate the entries below the pivot in column 2:
[tex]\[ \left[\begin{array}{ccc|c} 1 & -0.6667 & 0.3333 & 3.6667 \\ 0 & 1 & 7 & -22 \\ 0 & 0 & -2 & 6 \end{array}\right] \][/tex]
- Normalize the third row by dividing by the pivot element (-2):
[tex]\[ \left[\begin{array}{ccc|c} 1 & -0.6667 & 0.3333 & 3.6667 \\ 0 & 1 & 7 & -22 \\ 0 & 0 & 1 & -3 \end{array}\right] \][/tex]
3. Perform back-substitution to find the values of [tex]\(x, y,\)[/tex] and [tex]\(z\)[/tex].
- From the third row:
[tex]\[ z = -3 \][/tex]
- Substitute [tex]\(z = -3\)[/tex] into the second row equation:
[tex]\[ y + 7(-3) = -22 \implies y - 21 = -22 \implies y = -1 \][/tex]
- Substitute [tex]\( y = -1 \)[/tex] and [tex]\( z = -3 \)[/tex] into the first row equation:
[tex]\[ x - 0.6667(-1) + 0.3333(-3) = 3.6667 \implies x + 0.6667 - 1 = 3.6667 \implies x + 0.6667 = 4.6667 \implies x = 4 \][/tex]
So, the solution to the system of equations is:
[tex]\[ (x, y, z) = (4, -1, -3) \][/tex]
Thank you for participating in our discussion. We value every contribution. Keep sharing knowledge and helping others find the answers they need. Let's create a dynamic and informative learning environment together. For clear and precise answers, choose IDNLearn.com. Thanks for stopping by, and come back soon for more valuable insights.